Pengaruh Social Media Marketing, Electronic Word of Mouth, dan Customer Experience Terhadap Repurchase Intention Produk Make Over - Shifa Nur Aini; Ajeng Aquinia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines how the influence of Social Media Marketing, Electronic Word Of Mouth, and Customer Experience affects Repurchase Intention of Make Over products. Using a quantitative approach used in this study with a non-probability sampling method and purposive sampling technique involving 100 respondents who are active Make Over consumers through TikTok social media based on certain criteria. Data were collected through online questionnaires with a Likert measurement scale. Where the results of this study are in the form of numbers processed using SPSS software with validity, reliability, multiple linear regression, and t-test and f-test. The results of the study show that Social Media Marketing, Electronic Word Of Mouth, and Customer Experience have a simultaneous and significant influence on Repurchase Intention. These findings indicate that digital marketing strategies through social media, recommendations from other consumers, and positive customer experiences play an important role in encouraging consumer repurchase intentions for Make Over products. This study provides strategic implications for companies in designing digital-based marketing strategies to maintain customer loyalty.